A meta-analysis on plant growth and heavy metals uptake with the application of 2,4-epibrassinolide in contaminated soils - Kuiju Niu; Hong Xiao; Yong Wang; Ting Cui; Chunxu Zhao (Ecotoxicology and Environmental Safety)
The application of 2,4-epibrassinolide (EBR) is considered an effective and environment friendly method to improve plant growth under heavy metal (HM) stress, which is crucial for crop productivity and environmental phytoremediation. This meta-analysis evaluated plant responses to exogenous EBR under HM stress by compiling data from 73 studies, including 2480 observations. Results showed that the most significant effects of exogenous EBR on plant growth and HM uptake parameters were observed on shoot/root length (47.9 %) and HM concentration in plant tissues (-32.9 %). EBR application enhanced photosynthesis and the mitigation of oxidative damage by significantly boosting antioxidant enzyme activity, non-enzymatic antioxidants, and metabolites. Exogenous EBR induced the largest percentage changes in plant growth and HM uptake under nickel stress, with an average increase of 57.5 % and a decline of 38.5 %, respectively. The greatest effects of exogenous EBR on plant growth and HM uptake parameters were observed in plants of the Cruciferae family, while the lowest effects were in the Gramineae family. In terms of EBR application characteristics, seed soaking with lower EBR concentrations (≤ 1 nM) is recommended for crop production in HM-contaminated soils. These findings underscore the potential of exogenous EBR in achieving sustainable agriculture and environmental phytoremediation in HM-contaminated soils.